Barber Say Syndrome (A new case report) - Mehrdad Rezaei; Susan Zamani; Hourvash Haghighinejad (Wolters Kluwer Medknow Publications, 2019)
Barber Say syndrome (BSS) is a rare ectodermal dysplasia with neonatal onset characterized by congenital generalized hypertrichosis, atrophic skin, ectropion and macrostomia. A literature review showed less than 20 previously reported cases of Barber Say syndrome. This presentation reports a one day old female with syndrome face, low hairline, coarse face, macrostomia, thin upper lip, bilateral ectropion and hypertelorism, hypertrichosis, senile skin appearance, hypoplastic nipples and one area of mild skin atrophy. These findings are consistent with BSS.